2018
DOI: 10.1111/bld.12258
|View full text |Cite
|
Sign up to set email alerts
|

Do group interventions help people with autism spectrum disorder to develop better relationships with others? A critical review of the literature

Abstract: Accessible summary• Lots of people with autism find it difficult to make friends and have relationships.• There are lots of different groups that can help people with autism to learn social skills and how to make friends.• Some of the groups were specially designed for people with a learning disability as well as autism.• The groups can help support people to talk about their emotions, talk to other people about their thoughts and feelings and practise talking to other people.• This paper found that social ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…That is, students with a high level of empathy have higher acceptance of peers with disabilities in inclusive settings. This is in line with and strengthens further the results obtained by existing studies (e.g., Miller, 2013 ; Atkinson-Jones and Hewitt, 2019 ). The studies showed that the ability to enter into another individual's thoughts and feelings is important to develop in order to achieve a more inclusive attitude toward students with disabilities.…”
Section: Discussionsupporting
confidence: 93%
“…That is, students with a high level of empathy have higher acceptance of peers with disabilities in inclusive settings. This is in line with and strengthens further the results obtained by existing studies (e.g., Miller, 2013 ; Atkinson-Jones and Hewitt, 2019 ). The studies showed that the ability to enter into another individual's thoughts and feelings is important to develop in order to achieve a more inclusive attitude toward students with disabilities.…”
Section: Discussionsupporting
confidence: 93%
“…Autism-specific factors, such as difficulties communicating needs or maintaining structure (14,16) are related to the inaccessibility of health care. The advantages of group-based interventions for individuals with ASD have been suggested in several studies (17)(18)(19)(20) but there are several barriers to participation. Some people with ASD refrain from using public transport to health care facilities due to perceptual sensitivity (15).…”
Section: Introductionmentioning
confidence: 99%
“…Research indicates that children and adolescents with MID/BI have fewer self-regulation abilities than their typically developing peers ([ 52 , 53 ]), and that they also have difficulties regarding emotion regulation, cognition, behaviour, and physiology in response to stressful events or circumstances [ 49 ], which might point towards specific difficulties in dealing with emotions and prosocial behaviour ([ 5 , 50 , 54 ]). Notably, at least three reviews showed that lack of empathy and/or prosocial behavior in individuals with ASD can be treated effectively, including those with mild and moderate intellectual disability ([ [60] , [61] , [62] ]). Finally, there is support from research that adolescents with MID/BI experience lower levels of angry mood in their daily life compared to their peers without intellectual disabilities [ 54 ].…”
Section: Discussionmentioning
confidence: 99%